(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
A further understanding into the interplay of the reference rate, inflow of capital from non-residents of the country and unemployment within the Ghanaian economy was sought by this study. To achieve this, secondary data from 2003 to 2023 were utilized. Three specific objectives were addressed by the research work. To begin with, the effect of the base rate and prior capital inflows from foreigners on future investments in Ghana was assessed. The results indicated that while a direct influence on future investments was made by the reference rate and past investments from non-residents, a more deterministic significance was by previous investments. Second, the effect of prior capital inflows by foreigners and previous levels of unemployment on the current levels of the base rate was probed. The reference rate that was set by the central bank of Ghana was found to be more dependent on lagged foreign direct investments than on past unemployment levels. This showed that the central bank was more willing to mitigate the risk associated with inflation than to stabilize the labor market. Lastly, the influence of the reference rate and unemployment from previous years on future unemployment was determined. An analysis of the impact of prior levels of unemployment and the rate set by the central bank on the unemployment rate revealed that a notable effect on the level of unemployment in Ghana was had by the monetary policy rate.